(untitled) (Research, Society and Development, 2020)
Innovations in the health field have revolutionized the doctor-patient relationship. In this context, the worldwide technological advance has reinforced the importance of the relationship between medicine and technology, and in this way, telemedicine emerges as an alternative in coping with the pandemic caused by the new coronavirus. The objective is to identify the challenges that permeate the use of telemedicine and the impact of physical distance from the doctor-patient relationship during the pandemic caused by SARS-Cov-2. The search identified 24 articles, of which 12 were repeated and 4 escaped the proposed theme. Thus, after applying the pre-established inclusion and exclusion criteria, 5 studies remained. Among the selected publications, two are original articles, two are reflection articles, and one is a review article. In that, the prevalence of articles in the English language was observed, representing 87.5% of the total, when compared to the Spanish language (12.5%). All those who were elected for analysis were in 2020. The traditional relationship between the doctor and the patient is necessary for the development of the diagnosis, treatment and prevention of various diseases, however, this has undergone changes and innovations in recent times, mainly due to the advent of Covid-19, which changed this relationship. The study showed that there are still many barriers to be overcome in the context of the use of telemedicine in the field of health, practice presents some obstacles regarding its performance, especially when there is a need for a physical examination and intervention in more serious conditions.